Village poultry production systems in the central highlands of Ethiopia - Dessie, Tadelle; Ogle, B. (Springer, 2001)
Participatory rural appraisal (PRA), supported by checklists and intensive case studies on individual households, was carried out in three villages at three different altitudes in the central highlands of Ethiopia. The chicken production system in each village is described and the problems are discussed. More than 60% of the families kept chickens, and in most cases the women owned and managed the birds and controlled the cash from the sales. The production systems followed were mainly low-input and small-scale, with 7-10 mature birds per household, reared in the back yards with inadequate housing, feeding and health care. The average egg production per clutch was 15-20, with 3-4 clutches per year. The mean number of eggs set per bird was 12.9 +/- 2.2 (n = 160), depending on the size of the bird and season, and the hatching rate was 80.9% +/- 11.1%, range 44%-100% (n = 160). Poultry meat and eggs were generally accepted and appreciated in all three villages. In addition to the small amount of cash income they provide, scavenging chickens have nutritional, cultural and social functions. The flock composition, price of poultry and poultry products, disease outbreaks and hatching of chicks were strongly affected by season. Disease was cited as the most important problem by most of the members of the community, followed by predation, lack of feed, poor housing, insufficient water and parasites. Disease periodically decimated the flocks, and consequently, about 50% of the eggs produced were incubated in order to replace the birds that had died. The major source of loss in the system was the high mortality of chicks (61%) that occurred between hatching and the end of brooding at 8 weeks of age. The system was characterized by no or few inputs and a low output level. The major input was the cost of foundation stock, but after that virtually no cost was involved. The major source of feed for the birds was from the scavenging feed resource base, which comprised table leftovers, small grain supplements and anything edible from the immediate environment.